International perspectives on the youth labor market emerging research and opportunities - Amine, Samir (Advances in business strategy and competitive advantage., 2020)
""This book explores the state of the youth labor market and focuses on the inequalities of access to employment and the precariousness of which young people suffer"--Provided by publisher"--